6.3 Solutions 277
Substituting (3) in (1) and (2)
m
2
(
¨
X
1
+
¨
X
2
) +
mg
2b
(X
1
+ X
2
) + kX
2
= 0(4)
m
2
(
¨
X
1
−
¨
X
2
) +
mg
2b
(X
1
− X
2
) − kX
2
= 0(5)
Adding (4) and (5)
m
¨
X
1
+
mg
b
X
1
= 0(6)
which is a linear equation in X
1
alone with constant coefficients.
Subtracting (5) from (4), we obtain
m
¨
X
2
+
mg
b
+ 2k
X
2
= 0(7)
This is again a linear equation in X
2
as the single dependent variable. Since
the coefficients of X
1
and X
2
are positive, both (6) and (7) are differential
equations of simple harmonic motion having frequencies ω
1
=
g
b
and
ω
2
=
g
b
+
2k
m
. Thus when equations of motion are expressed in normal
coordinates, the equations are linear with constant coefficients and each con-
tains only one dependent variable.
We now calculate the energy in normal coordinates. The potential energy
arises due to the energy stored in the spring and due to the position of the
body.
V =
1
2
k(x
1
− x
2
)
2
+ mgb(1 − cos θ
1
) + mgb(1 − cos θ
2
) (8)
Now b(1 − cos θ
1
) = b
θ
2
1
2
=
x
2
1
2b
Similarly b(1 − cos θ
2
) =
x
2
2
2b
Hence V =
k
2
(x
1
− x
2
)
2
+
mgx
2
1
2b
+
mgx
2
2
2b
(9)
Kinetic energy T =
m
2
˙x
2
1
+˙x
2
2
(10)
Although there is no cross-product term in (10) for the kinetic energy, there
is one in the potential energy of the spring in (9). The presence of the cross-
product term means coupling between the components of the vibrating system.
However, in normal coordinates the cross-product terms are avoided. Using
(3) in (9) and (10)